Adipose tissue inflammation by intermittent hypoxia: mechanistic link between obstructive sleep apnoea and metabolic dysfunction. (25th January 2017) - Ryan, Silke
Abstract : Phenotypic modulation of the adipose tissue by intermittent hypoxia (IH). The schematic diagram shows how IH in interaction with obesity leads to pro‐inflammatory changes and dysfunction of the adipose tissue. Healthy adipose tissue is characterized by small adipocytes and infiltration of M2–anti‐inflammatory macrophages and CD4 + regulatory T‐cells leading to the production of anti‐inflammatory adipokines. With IH treatment, CD8 + cytotoxic T‐cells are recruited and macrophages shift towards a M1–pro‐inflammatory phenotype forming crown‐like structures (CLS) surrounding necrotic adipocytes. The consequence of these alterations is the upregulation and secretion of numerous pro‐inflammatory adipokines and lipolysis with free fatty acid flux into the circulation collectively promoting impairment of the insulin‐signalling pathway leading to metabolic dysfunction. (IL, interleukin; TNF‐α, tumour necrosis factor alpha; MCP‐1, monocyte chemoattractant protein‐1; NAMPT, nicotinamide phosphoribosyltransferase; CXCL5, C‐X‐C motif chemokine ligand 5; FFA, free fatty acids). Abstract: Obstructive sleep apnoea (OSA) is a highly prevalent condition and recognized as a major public health burden conveying a significant risk of cardiometabolic diseases and mortality. Type 2 diabetes (T2D), insulin resistance (IR) and glucose tolerance are common in subjects with OSA and this association is at least in part independent of the effects of obesity. Continuous positive airway pressure (CPAP) is the treatment of choice for the majority of patients with OSA but the benefit of CPAP on glycaemic health is uncertain. Thus, a greater understanding of the mechanisms by which OSA leads to metabolic dysfunction might identify novel therapeutic approaches. Intermittent hypoxia (IH), a hallmark feature of OSA, likely plays a key role in the pathogenesis and experimental studies using animal and in vitro models suggest that IH leads to pancreatic β‐cell dysfunction and to insulin resistance in the insulin target organs liver, skeletal muscle and adipose tissue. In particular, IH induces a pro‐inflammatory phenotype of the visceral adipose tissue with polarization of adipose tissue macrophages towards a M1–pro‐inflammatory subtype, upregulation and secretion of numerous pro‐inflammatory adipokines and subsequent impairment of the insulin‐signalling pathway, changes which bear a striking similarity to adipose tissue dysfunction seen in obesity. In this review, the available evidence linking IH with metabolic dysfunction is explored with a special emphasis on the adipose tissue in this process.